Implementing the IBM - Barnes, Joshua (IBM Press, 2007)
The Authoritative, Best-Practice Guide to Improving Development Processes with IBM® Rational Unified Process® (RUP®) This book delivers all the knowledge and insight you need to succeed with the IBM Rational Unified Process and Solutions. Joshua Barnes presents a start-to-finish, best-practice roadmap to the complete implementation cycle of IBM RUP-from projecting ROI and making the business case through piloting, implementation, mentoring, and beyond. Drawing on his extensive experience leading large-scale IBM RUP implementations and working with some of the industry's most recognized thought leaders in the Software Engineering Process world, Barnes brings together comprehensive "lessons learned" from both successful and failed projects. You'll learn from real-world case studies, including actual project artifacts. Whether you're an executive, software professional, or consultant, this book will help you continuously improve the maturity of your development processes-and reap the benefits: better quality, faster delivery, and more business value. After reading this book you will be able to · Get past the myths of software process improvement to focus on what's truly practical · Identify and evaluate your best candidate process solutions · Objectively project the ROI achievable with IBM R UP and IBM Rational solutions · Develop funding models, business cases, and executive support · Recruit, staff, organize, and motivate your implementation team · Plan for effective integration, process alignment, and change management · Choose the right pilots, learn the right lessons, and develop effective adoption models · Move quickly to successful program-level implementation · Set maturity level goals for process and tool utilization · Map "End States" for both quantity and quality · Plan for training and mentoring-and understand the distinct role of each · Keep the momentum going after your implementation is complete Link to www.upmentors.com, where you can download actual sample implementation documents-not just templates! www.ibmpressbooks.com Preface xvii Acknowledgments xxiii About the Author xxv Chapter 1: Evaluating Process Solutions 1 Chapter 2: Your First Steps Toward Implementing RUP and IBM Rational Solutions 17 Chapter 3: Assessing Your Organization and Building Your Business Case for Organizational Change 29 Chapter 4: Implementation Team 49 Chapter 5: Settin ...